The effectiveness of google sites on the concept mastery of high school students - Munawirah, Rini; Sitompul, Stepanus Sahala; â Hamdani, â Hamdani (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2024)
This research investigates the effectiveness of using Google Sites in improving high school students' mastery of physics concepts. The research method used was quasi-experimental with a pretest-posttest control group design. The research subjects consisted of two classes: the experimental class, which used Google Sites, and the control class, which used conventional methods. Data was collected through concept mastery tests given before and after treatment. The research results showed that the experimental class's average posttest mastery of concepts was higher than in the control class. The independent t-test indicated a significant difference in the pretest-posttest difference between the two classes. The n-gain calculation shows that the experimental class is quite effective, while the control class is in the ineffective category. This research concludes that using Google Sites in physics learning effectively increases students' mastery of concepts. It is recommended that these media be optimized in the learning process by providing tutorials on using them before learning begins and preparing practical tools and materials well. Optimizing Google Sites can support a more effective and efficient learning process and significantly improve student learning outcomes.